Gesture Influences Resolution of Ambiguous Statements of Neutral and Moral Preferences - Hinnell, Jennifer; Parrill, Fey (Frontiers in Psychology, 2020)
When faced with an ambiguous pronoun, comprehenders use both multimodal cues and linguistic cues to identify the antecedent. While research has shown that gestures facilitate language comprehension, improve reference tracking, and influence the interpretation of ambiguous pronouns, literature on reference resolution suggests that a wide set of linguistic constraints influences the successful resolution of ambiguous pronouns and that linguistic cues are more powerful than multimodal cues. To address the importance of gesture as a cue in reference resolution relative to cues in the speech signal, the authors previously investigated the comprehension of contrastive gestures that indexed abstract referents and found that such gestures did facilitate the resolution of ambiguous statements. In this study, we extend this work to investigate whether the effect of gesture on resolution is diminished when the gesture indexes a statement that is less likely to be interpreted as the correct referent. Participants watched videos in which a speaker contrasted two ideas that were either neutral or moral. A gesture to the left or right side co-occurred with speech expressing each position. In gesture-disambiguating trials, an ambiguous phrase was accompanied by a gesture to one side or the other. In gesture non-disambiguating trials, no third gesture occurred with the ambiguous phrase. Participants were more likely to choose the idea accompanied by gesture as the stimulus speaker’s preference. We found no effect of scenario type; regardless of whether the linguistic cue expressed a view that was morally charged or neutral, observers used gesture to understand the speaker’s opinion.